ANALISIS KEPUASAN MASYARAKAT TERHADAP SISTEM INTEGRASI TRANSPORTASI UMUM DI DAERAH KHUSUS JAKARTA - Sevana Esha Ariswara; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
Jakarta faces traffic congestion challenges due to its high population density and urban mobility demands, prompting the DKI Jakarta Provincial Government to develop an integrated public transportation system connecting MRT, LRT, and Transjakarta through the JakLingko program under Governor Regulation No. 68 of 2021. This study aims to analyze the level of public satisfaction with the integrated public transportation system in Jakarta and identify obstacles faced by users. The research employs a mixed-method approach with a sequential explanatory design, involving 125 active users of 2–3 integrated transportation modes through questionnaires, interviews, and field observations. The research instrument was developed based on SERVQUAL theory, measuring five service quality dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy, using the Guttman scale. Results show an overall satisfaction rate of 92.1%, with 78.4% of respondents being very satisfied. The Responsiveness dimension achieved the highest score with 100% officer alertness, followed by Tangibles and Empathy at 96% each. Main obstacles include Transjakarta fleet delays (45.6%), incomplete route coverage (40%), and limited fleet availability (26.4%). The study concludes that Jakarta's integrated public transportation system has achieved high satisfaction levels but requires continuous improvement in service frequency, route expansion, and payment system optimization.